A Multi-Zone Unsteady Heat Transfer Model for an Open Volumetric Air Receiver: A Step Towards Scale-Up and Design Optimization. (1st August 2022) - Kumar, Vishwa Deepak; Singh, Gurveer; Chandra, Laltu; Mukhopadhyay, Sudipto; Shekhar, Rajiv
Highlights: A multi-zone model for unsteady heat transfer is proposed for an open volumetric air receiver. The model includes all the modes of heat transfer in receiver internals. Detailed investigations are performed to identify the important parameters. Recommendations are made for the scale-up receiver design. Abstract: A comprehensive, multi-zone, unsteady heat transfer model is developed for a straight absorber pore-based open volumetric air receiver. This includes heat exchange between the porous absorbers, absorbers and receiver casing, and absorbers and return air. The validation revealed its predictive capability within an uncertainty of ±7%. The model is used for the scale-up of receiver design with several intermediate absorber layers. The major recommendations for scale-up are a) multiple absorber layers is beneficial for mitigating thermal stress, b) higher flux concentration is required for non-volumetric heating, to achieve the desired air temperature, compared to volumetric heating, c) air return ratio should be 0.6, d) absorber porosity should be 0.6 for volumetric heating and higher for non-volumetric heating, e) absorber gap to length ratio should be 0.15 -0.25, f) the radiative heat loss is substantial for non-volumetric heating; therefore, the exposed surface area to ambient should be reduced, and g) absorber diameter to length ratio should be 1-2. The developed approach is generic and adaptable for the different open volumetric air receiver designs.